PERANCANGAN REBRANDING BAROKAH AIRCOND - Subron Jamilan, Muhammad Urip; Martin Setyawan; Birmanti Setya Utami (AKSA: Jurnal Desain Komunikasi Visual, 2023)
This design aims to rebrand Barokah Aircond's visual identity, and produce a visual identity design as a corporate image communication medium. The method in this design uses 5 phases of Design Thinking consisting of Empathize, Define, Ideate, Prototype and Testing. The data extracted in this research cover problems as a theoretical basis related to logo design and the company's needs regarding visual identity. There is a design because currently, the Barokah Aircond company has not been able to display the company's image through a visual identity which is a threat amid the many competitors engaged in similar businesses. The result of this design is a visual identity in the form of a logo and supporting media that can be used as a company promotion media.